Patrząc na mapę, spoglądam w nicość… Wokół melancholii i nudy w wybranych tekstach prozatorskich Andrzeja Stasiuka - Lech, Jacek (Tematy i Konteksty, 2015)
The paper aims at showing the link between Andrzej Stasiuk’s selected prose texts and the beauty of melancholy. The way in which melancholy functions in literature in the period of postmodernity was the starting point for our considerations. We have focused on the way this notion has been radically changed by postmodernism and how it has been deprived of its spiritual importance. The beauty of melancholy is part of Stasiuk’s novel in two ways. First and foremost, this concerns the texts about travelling in which it seems to be a reflection on reality and is inextricably linked with the categories of memory and existence. As stressed by Stasiuk, melancholy has its root in suspicion concerning reality tactics. It may be regarded as ‘melancholy of the way’ and in this sense it is accompanied by a spiritual burden directed against postmodernism. In turn, in 'Opowieści galicyjskie' and 'Zima' it is equated with the boredom and humdrum nature of small-town life. Deprived of its spiritual being it manifests itself as an example of existential torpor and stagnation which are part and parcel of Stasiuk’s characters who – in turn – are painfully stricken by bad fate and function thoughtlessly in lives which they fail to run away from.